Implementation of Restrictiuons on Community Activities (PPKM) Policy Analysis Level 1-4 In Dealing With The Covid-19 Outbreak In Indonesia - Saraswati, Indarti; Muzdalifah, Aida; Herawati, Agustin Rina; Kismartini, Kismartini (Ridwan Institute, 2021)
The Indonesian government has implemented several policies in dealing with COVID-19 cases in Indonesia. One of the policies implemented is PPKM level 1-4. The level in this policy is adjusted to the conditions of each region. The research method used is descriptive qualitative.Â This research comes from data sources in the form of scientific journals, book literature, official websites which are described through descriptive analysis that describes the implementation of PPKM policies level 1-4 in Indonesia. The results of this study show that the leveled PPKM policy is the most effective policy in reducing the number of COVID-19 in Indonesia, as evidenced by the decrease in levels in various regions in Indonesia. The involvement of various parties, both the government and the community, is the key to success in implementing this policy